Prevalence of Neuropathic Pain and the Need for Treatment - Pat Morley-Forster (Pain Research and Management)
Recent publications have suggested that more than two million adults in the United States suffer from neuropathic pain, but this number seems to be a significant underestimate. The prevalence of neuropathic pain from diabetes and postherpetic neuralgia alone, using the most conservative estimates of incidence, would equal two million Americans. Lesions of the nervous system responsible for pain genesis can occur either in the central or the peripheral nervous system. The most common causes of peripheral neuropathic pain syndromes worldwide are diabetes, HIV infection, cancer-related neuropathy (due to tumour invasion, surgical nerve damage, radiation or chemotherapy-induced nerve damage) and lumbar degenerative disc disease. Other less common, but significant, sources of suffering are postherpetic neuralgia, complex regional pain syndrome, phantom limb pain and postsurgical nerve trauma. Central neuropathic pain can be caused by stroke (infarct or hemorrhage), multiple sclerosis, spinal cord injury and syringomyelia. Certain pain syndromes such as trigeminal neuralgia and vulvodynia, although clearly neuropathic and a source of tremendous suffering, are not discussed in the present article due to space constraints. There is an unmet need for the treatment of neuropathic pain as evidenced by reports of pain despite the use of opioids and anticonvulsants, continuing psychological difficulties, lack of access to treatments and patients seeking access to complementary therapy.